2022
DOI: 10.1002/app.53029
|View full text |Cite
|
Sign up to set email alerts
|

Development of high‐performance partially biobased thermoset polyester using renewable building blocks from isosorbide, 1,3‐propanediol, and fumaric acid

Abstract: Research on biobased thermoset resins has been overlooked when compared with the rapid progress on biobased thermoplastics. The objective of this work was to develop unsaturated polyester prepolymers based on building blocks derived from renewable raw materials, namely, biobased isosorbide, 1,3-propanediol, and fumaric acid, with petroleum-derived phthalic anhydride. The prepolymers developed herein behaved as low-molecular weight macromolecules (oligoesters), with M n varying between 1.2 and 1.5 kDa, but achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The starting degradation temperature (T onset ) and temperature with the highest degradation rate (T max ) were higher for the biobased resin (T onset = 137.0−181. 4 2, entry 6). The residual at 600 °C was slightly higher for the cured biobased resin (7.1%) prepared according to the best of the studied parameter settings than VER (4.5 and 5.1%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The starting degradation temperature (T onset ) and temperature with the highest degradation rate (T max ) were higher for the biobased resin (T onset = 137.0−181. 4 2, entry 6). The residual at 600 °C was slightly higher for the cured biobased resin (7.1%) prepared according to the best of the studied parameter settings than VER (4.5 and 5.1%).…”
Section: Resultsmentioning
confidence: 99%
“…29 Various physical, 30 chemical, 31,32 and biological processes 33,34 have been developed to extract useful biobased monomers from lignocellulosic biomass. 35−37 This article is licensed under CC-BY 4 The family of polyesters has several advantages in providing macromolecular components in thermoset resins, such as facile preparation, 38 low cost, potential biodegradability, 39 and tunable properties. 40 There have been several reports demonstrating the development of entire biobased resins; for instance, Brannstrom et al used itaconic acid (IA), succinic 41 Nevertheless, the cured resin demonstrated increased T g ∼ 12 to ≤100 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…vitrimers) which render re-processable thermosets possible [20][21][22] (for general readings on thermosets composed of dynamic networks see [23][24][25][26]). We will not review the literature on bio-based UPR here in detail, but we note that while all efforts remain as an excellent proof of concept, the detailed inspection of the accounts revealed only a handful contributions [27][28][29][30][31][32][33][34][35][36][37] which reported mechanical properties in agreement with industrial standards [38,39] (For a comprehensive overview of bio-based UPR see Supporting Information). These include, for example, studies with modified soybean oil [31][32][33][34], which led to UPR possessing an E-modulus of about 2.5 GPa, tensile strengths of 44 MPa, and flexural strengths of 80 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…vitrimers) which render re‐processable thermosets possible [20–22] (for general readings on thermosets composed of dynamic networks see [23–26]). We will not review the literature on bio‐based UPR here in detail, but we note that while all efforts remain as an excellent proof of concept, the detailed inspection of the accounts revealed only a handful contributions [27–37] which reported mechanical properties in agreement with industrial standards [38, 39] (For a comprehensive overview of bio‐based UPR see Supporting Information).…”
Section: Introductionmentioning
confidence: 99%